Poverty Incidence Of Different Social Groups In The Northern States Of Malaysia - Golshani Iran, Mohammad Darabi (2017)
This study assesses the poverty incidence among the different social groups in strata, ethnic groups, income level, and education and investigates the factors that influence poverty of the different social groups in the northern states of Malaysia. For this purpose three Poverty Line Income (PU); National PU, Asian Development Bank (ADB) PU and ADB vulnerability adjusted PU determined to specify the poor. This study uses the Household Income Survey (HIS) data that was conducted by the Department of Statistics for 2009 and 2012 for northern states of Malaysia. Data has shown that Malaysia has been very successful in eradicating poverty from more than fifty percent in the early 70s to less than 10 percent now. Nevertheless, pockets of poverty still exist, particularly in the rural areas and in a few states in East Malaysia, East Coast and the Northern States.